The role of platelets in thrombus fibrosis and vessel wall remodeling after venous thrombosis. (29th November 2020) - DeRoo, Elise; Martinod, Kimberly; Cherpokova, Deya; Fuchs, Tobias; Cifuni, Stephen; Chu, Long; Staudinger, Caleb; Wagner, Denisa D.
Abstract: Purpose: Platelets are known to play an important role in venous thrombogenesis, but their role in thrombus maturation, resolution, and postthrombotic vein wall remodeling is unclear. The purpose of this study was to determine the role that circulating platelets play in the later phases of venous thrombosis. Methods: We used a murine inferior vena cava (IVC) stenosis model. Baseline studies in untreated mice were performed to determine an optimal postthrombotic time point for tissue harvest that would capture both thrombus maturation/resolution and postthrombotic vein wall remodeling. This time point was found to be postoperative day 10. After undergoing IVC ultrasound on day 2 to confirm venous thrombus formation, mice were treated with a daily injection of platelet‐depleting antibody (anti‐GP1bα) to maintain thrombocytopenia or with control IgG until postoperative day 10, at which time IVC and thrombi were harvested and thrombus length, volume, fibrosis, neovascularization, and smooth muscle cell invasion analyzed. Vein wall fibrosis and intimal thickening were also determined. Results: Mice that were made thrombocytopenic after venous thrombogenesis had thrombi that were less fibrotic, with fewer invading smooth muscle cells. Furthermore, thrombocytopenia in the setting of venous thrombosis resulted in less postthrombotic vein wall intimal thickening. Thrombus volume did not differ between thrombocytopenic mice and their control peers. Conclusions: This work suggests that circulating platelets contribute to venous thrombus maturation, fibrosis, and adverse vein wall remodeling, and that that inhibition of platelet recruitment may decrease thrombus and vein wall fibrosis, thus helping thrombolysis and preventing postthrombotic syndrome.